PENERAPAN METODE FUZZY MAMDANI UNTUK MENENTUKAN TINGKAT KUALITAS AIR SUNGAI LINTAS PROVINSI DI PULAU JAWA - Maya Widyastiti (EKOLOGIA, 2018)
This research aims to determine of river water quality status in the province of Java, including Banten, DKI Jakarta, West Java, Central Java, Yogyakarta and East Java. The data used are secondary data obtained from the ministry of environment and forestry in 2015. In this research, Fuzzy Mamdani method will be used to give solution of river water quality status. Parameters measured and observed are the parameters of Total Suspended Solid (TSS), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), and Chemical Oxygen Demand (COD).Top of Form Based on fuzzy mamdany , Status of river water quality status in DKI Jakarta and West Java have been heavily pollution. Banten province was in mild pollution to moderate pollution. Central Java was in light pollution to heavily pollution. DI Yogyakarta was in mild pollution, and East Java was in mild pollution to moderate pollution.Key words: Fuzzy Mamdani, river water pollution, water quality status